Variation in percentage of medullated fibres and colorimetry in white Huacaya and Suri alpaca fibre - Roldan-Juarez, Jesús (2024)
The aim of the study was to evaluate the variability of the percentage of medullated fibres, according to sex and location and to compare the colorimetric characteristics in white fibre from Huacaya and Suri alpaca. The study was carried out in two communities (Juntaya in the Oropesa district and San Juan in the Sabaino district) in the province of Antabamba, Apurímac region (Peru), located between 3950 and 4543 meters above sea level. In total, 451 (Huacaya = 410 and Suri = 41) fibre samples (10 g) were taken from the mid side area. The medullated fibres (%) and the mean fibre diameter (µm) were evaluated using the Fiber Med device. For the colour analysis, a spectrometer coupled to an integrating sphere was used and for the characterization of the chemical bands, an FTIR spectrophotometer. The percentage of total medullation, continuous medullation and strongly medullated fibres were greater in female Huacaya alpacas (p<0.01). The mean diameter of medullated and non-medullated fibres differed depending on the location, while the mean fibre diameter and mean diameter of medullated fibres were higher in males (p<0.01). The colorimetric parameters of luminosity (L*), chromaticity (C*) and tone (Hº) were similar (p>0.05) in the fibres of the two groups of alpacas. In conclusion, in Huacaya alpaca there is variability in the percentage of continuous medullation and mean fibre diameter, depending on sex and location, but the colorimetric characteristics of white fibres are like those of the Suri.